Legal Instruments for Stimulating Interregional Competition for Investment - Lapo, Valentina Fedorovna (Economy of Regions, 2020)
In order to study the role of legal instruments in stimulating the spatial competition and economic integration of the entities of the Russian Federation, it is necessary to examine a system of interacting regions. Regional laws on investment promotion have been acting and improvingfor a long time. Thus, the paper examines the set of these laws and their impact on interregional integration and regional competition. The study identifies three levels of competition: the all-Russian competition, competition within federal districts, and competition between neighbouring regions. As benefits as instruments for attracting investments are applied in regions, they influence the decision to invest in other regions. Therefore, the developed econometric model of dynamic panel regression of investments assesses the economic interaction between the regions. The model “the dynamic panel regression of investments taking into account the competition between the regions” (DPRI-CR) includes stimulation instruments and spatially weighted variables related to regional benefits. The indicators for assessing regional spatial interaction are based on the coefficients of the similarity of the legal systems in two regions. Testing of the DPRI-CR demonstrates the exiting external positive, negative and neutral effects of investment benefits that significantly differ depending on the level of competition. An increase in the regional economic integration causes an increase in the positive and negative effects. Consequently, the investment policies that are aimed at increasing economic interaction should take into account the regions economic integration with the economies of the neighbouring regions, regions of the federal district and other entities of the country. The regions, which are closely integrated with the majority of regions, have the most opportunities to use the external effects. They can apply either “driving force of the economy” instruments to enhance positive effects or “driving force of the progress” instruments to increase their competitive position.